2006
DOI: 10.1007/s10340-006-0121-1
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism of canola aphids in France in autumn

Abstract: In light of a recent increase in the aphid populations on young canola (Brassica napus) in autumn in Northwestern Europe, we carried out a survey of their parasitoid species during this season. The study was done in France from 1998 to 2001 using different sampling methods. Results highlighted the presence of two main species of Aphidiinae, Aphidius matricariae and Diaeretiella rapae (and to a lesser extent Aphidius ervi) on Myzus persicae, and of D. rapae on Brevicoryne brassicae. Nine other Aphidiinae specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 10 publications
2
22
0
1
Order By: Relevance
“…Also, L. testaceipes is a common parasitoid of Aphis craccivora Koch in urban landscapes ) and this species is one of the most common aphids in the alfalfa Welds in summer . Cereal aphids, especially R. maidis and R. padi, may act as an autumn and winter reservoir of D. rapae, the most common parasitoid of the Brevicoryne brassicae L. (Desneux et al 2006), the main pest of oilseed rape in the region. This means that cereals act as a reservoir of parasitoids that, moreover, interact with aphid populations on other important arable crops such as alfalfa, maize and oilseed rape, or even in orchards, another widespread component of the agricultural landscape of the NE Iberian Peninsula.…”
Section: Discussionmentioning
confidence: 99%
“…Also, L. testaceipes is a common parasitoid of Aphis craccivora Koch in urban landscapes ) and this species is one of the most common aphids in the alfalfa Welds in summer . Cereal aphids, especially R. maidis and R. padi, may act as an autumn and winter reservoir of D. rapae, the most common parasitoid of the Brevicoryne brassicae L. (Desneux et al 2006), the main pest of oilseed rape in the region. This means that cereals act as a reservoir of parasitoids that, moreover, interact with aphid populations on other important arable crops such as alfalfa, maize and oilseed rape, or even in orchards, another widespread component of the agricultural landscape of the NE Iberian Peninsula.…”
Section: Discussionmentioning
confidence: 99%
“…Although both species diVer in their behavioral responses to M. persicae on canola (Desneux et al 2004b), both appear well-adapted to this speciWc host-plant complex (Wilson and Lambdin 1987;Desneux et al 2005). In contrast, Aphidius ervi Haliday and A. colemani Viereck (Hymenoptera: Braconidae), both parasitoids of M. persicae that are abundant in European agricultural landscapes (Kavallieratos et al 2004;Lumbierres et al 2007), are respectively rarely found and not found at all to attack M. persicae in winter canola (Desneux et al 2006b;Desneux N. unpublished data). Yet, A. colemani is able to parasitize M. persicae on other cruciferous plants, such as cabbage (Kalule and Wright 2004;Langhof et al 2005) and can be reared successfully on M. persicae on winter canola under laboratory conditions (Storeck et al 2000;Colinet et al 2006).…”
Section: Introductionmentioning
confidence: 94%
“…Various parasitoid species attack M. persicae in cruciferous crops (Schlinger and Mackauer 1963;van Emden et al 1969) and more speciWcally, two aphidiine parasitoids: Aphidius matricariae Haliday (Hymenoptera: Braconidae) and Diaeretiella rapae McIntosh (Hymenoptera: Braconidae) (Desneux et al 2006b;Desneux N. unpublished data) which are dominant in winter canola Welds. Although both species diVer in their behavioral responses to M. persicae on canola (Desneux et al 2004b), both appear well-adapted to this speciWc host-plant complex (Wilson and Lambdin 1987;Desneux et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Our study showed A. ervi, T. complanatus, P. exsoletum and L. fabarum as potential candidate species which could provide biological control of their respective aphid hosts but more studies are needed in order to determine how to manage biological control programs (Desneux et al 2006). Finally, the broadly oligophagy of A. ervi and L. fabarum and the proximity of different crops surrounding alfalfa fields, may contribute to the spill-over of these parasitoid species from alfalfa to other crops in the area.…”
Section: Discussionmentioning
confidence: 96%